Disaster mitigation in Asia and the Pacific (Manila, 1991)
A ready reference handbook targeted at all disaster management officials, whether within government or outside. The handbook focuses on Southeast Asia and the Pacific, covering natural calamities ranging from earthquakes to volcanic eruptions and from cyclones to floods; it also describes principles and practices that are applicable to other areas and circumstances.
Dự báo và quản lý thảm họa
Keywords: Thảm họa,Quản lý tình trạng khẩn cấp,Disasters,Emergency management; Diện mạo kinh tế,Quốc hội Hoa Kỳ,Quốc hội Hoa Kỳ,Economic aspects,Congresses,Congresses; Châu Á,Châu Á,Asia,Asia